Is Board Gender Diversity Linked to Financial Performance? The Mediating Mechanism of CSR - Galbreath, Jeremy (Sage Publications, 2018)
© 2016, © The Author(s) 2016. The evidence for a positive, direct link between the representation of women on boards of directors and financial performance is tenuous. Given the importance of the gender diversity–financial performance debate, researchers are left to examine how, if at all, the two are linked. The present study takes the position that the link is indirect. Specifically, following stakeholder theory, an argument is made that women on boards’ attunement to stakeholder interests leads them to influence firms’ prosocial actions, which results in higher levels of corporate social responsibility (CSR). In turn, following the extant literature, CSR is expected to be positively linked to financial performance. Relying on a sample of Australia’s largest publicly traded firms, the results demonstrate that women on boards are linked to CSR and that CSR is linked to financial performance. However, in the mediation test, CSR appears to fully mediate the link between women on boards and financial performance. The results are discussed along with limitations and future research directions.